Side window cover and semiconductor light-emitting device

By directly bonding the translucent material with glass ceramics, and using a concave-shaped side window cover design, combining the airtight sealing technology of the sealing material layer and the gold-tin ring, the distance between the light emitting element and the exit surface is solved, and light leakage problems are achieved, thus achieving Highly efficient light extraction and good heat dissipation.

CN119404393APending Publication Date: 2025-02-07AGC INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380048296.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-24
Filing Date
2023-06-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, when designing side window covers, it is difficult to achieve a close distance between the light emitting element and the exit surface, and there is a problem of light leakage, and the manufacturing process is complicated.

Method used

The translucent material is used to directly bond with the glass ceramic to form a side window cover with a concave shape, and the airtight seal is achieved through the sealing material layer and the gold-tin ring, and integrated molding is achieved through blade cutting.

Benefits of technology

The distance between the light emitting element and the exit surface is achieved, the heat dissipation and the thickness of the package are improved, and light leakage is effectively suppressed, and productivity is also excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404393A_ABST
    Figure CN119404393A_ABST
Patent Text Reader

Abstract

The present invention relates to a side window cover which covers a light-emitting element and is sealed to a substrate on which the light-emitting element is provided, the side window cover having an upper wall part, four side wall parts, and a lower opening part and having an inverted concave cross-section, one of the four side wall parts being a window made of a translucent material, and the other side wall part being a window made of a translucent material. Three of the four side wall parts and the upper wall part are made of glass ceramic, and the light-transmitting material is directly bonded to the glass ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a side window cover and also to a semiconductor light emitting device hermetically sealed by the side window cover. Background Art

[0002] In recent years, electronic devices equipped with various light-emitting elements such as laser diodes have been used in various fields. Since airtight sealing is required depending on the type of light-emitting element, various sealing structures for sealing the light-emitting element have been studied in the past.

[0003] Laser diodes emit light in two ways: top surface emission and end surface emission. Compared with top surface emission, end surface emission has higher output.

[0004] Regarding this type of end-face light emission, Patent Document 1 discloses a light-emitting device as described below, namely, the light-emitting device comprises: a light-emitting element for emitting light; a first substrate on which the light-emitting element is mounted; a second substrate between which a sealed space for the light-emitting element is formed; and a light extraction window for extracting light emitted from the light-emitting element, wherein at least one of the first substrate and the second substrate has a cleavage property, and a window mounting surface for mounting the light extraction window serves as a cleavage surface.

[0005] Patent document 2 discloses an electric component mounting package including a flat substrate and one or more pedestals protruding from the surface of the substrate and having a mounting surface for mounting the electric component, wherein the substrate and the pedestals are integrally formed by ceramic.

[0006] Patent document 3 discloses a light source device as described below, namely, the light source device comprises a laser diode, a substrate having a main surface directly or indirectly supporting the laser diode, and a cover fixed to the substrate and covering the laser diode, the cover having a wall portion having an inner wall surface and an outer wall surface surrounding the laser diode, the inner wall surface having at least a light incident surface for laser light emitted from the laser diode and a first inclined surface, the outer wall surface having a light exit surface for laser light emitted from the laser diode, at least one of the light incident surface and the light exit surface being perpendicular to the optical axis of the laser light, and the first inclined surface being inclined toward the laser diode.

[0007] Patent Document 1: Japanese Patent Application Publication No. 2009-289775

[0008] Patent Document 2: International Publication No. 2018-030486

[0009] Patent Document 3: Japanese Patent Application Publication No. 2021-057459

[0010] However, the light emitting device described in Patent Document 1 has a structure in which the emission surface has a concavo-convex structure and the light extraction window is installed from the rear. Therefore, the second substrate and the light extraction window cannot be integrally formed, and the manufacturing process is complicated.

[0011] The package for mounting electric components described in Patent Document 2 has frames bonded to all four sides of the glass that becomes the emission surface, so it is necessary to provide a pedestal protruding from the substrate and mount the electric components on the pedestal. Therefore, the distance between the light-emitting point and the emission surface cannot be made close, and there is a limit to the requirements for good heat dissipation and thinning of the package.

[0012] The cover covering the laser diode of the light source device described in Patent Document 3 is entirely made of glass, which causes leakage of laser light. Among them, since laser light has high straightness, there is a particular concern of leakage from the surface opposite to the light emitting surface. Summary of the invention

[0013] Therefore, an object of the present invention is to provide a side window cover which is not necessarily required for a pedestal, can directly set a light emitting element on a substrate, can be integrally formed, and can suppress light leakage.

[0014] In order to solve the above-mentioned problems, one aspect of the side window cover according to the present embodiment is as follows.

[0015] A side window cover, relative to a substrate provided with a light emitting element, covers the light emitting element and is sealed to the substrate, wherein:

[0016] The side window cover has an upper wall portion, four side wall portions and a lower opening portion and has a concave cross-section.

[0017] One of the four side walls is a window made of a light-transmitting material.

[0018] Three of the four side walls and the upper wall are made of glass ceramics.

[0019] The light-transmitting material is directly bonded to the glass ceramic.

[0020] In addition, one aspect of the semiconductor light emitting device according to the present embodiment is as follows.

[0021] A semiconductor light emitting device, wherein:

[0022] The invention comprises a side window cover, a substrate and a light emitting element arranged on the substrate.

[0023] The side window cover has a sealing material layer on the lower end surface of the four side wall parts.

[0024] The sealing material layer is a layer composed of a metal film, and has an Ag layer or an Au layer on its outermost surface.

[0025] The side window cover and the substrate are integrated via the sealing material layer and the gold-tin ring, and the light-emitting element is hermetically sealed.

[0026] Among them, the above-mentioned side window cover has an upper wall portion, four side walls and a lower opening portion, and the cross-section is in an inverted concave shape. One of the above-mentioned four side walls is a window made of a light-transmitting material, three of the above-mentioned four side walls and the above-mentioned upper wall portion are made of glass ceramics, and the above-mentioned light-transmitting material is directly bonded to the above-mentioned glass ceramics.

[0027] According to the present invention, a pedestal is not necessary, and the light-emitting element can be directly arranged on the substrate. Therefore, the distance between the light-emitting point and the emission surface can be made short, and good heat dissipation and thinning of the package can be achieved. In addition, according to the present invention, a side window cover can be obtained by integral molding, so the productivity is excellent. In addition, because the light leakage suppression effect is also high, it is particularly suitable as a light-emitting element in the use of end-emitting laser diodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic perspective view showing one form of the side window cover according to the present embodiment.

[0029] Figure 2 is Figure 1 AA' line sectional view of the side window cover shown in FIG.

[0030] Figure 3 It is a bottom view showing one form of the side window cover according to the present embodiment.

[0031] Figure 4 This is a cross-sectional view showing one form of the side window cover according to the present embodiment.

[0032] Figure 5 It is a bottom view showing one form of the side window cover according to the present embodiment.

[0033] Figure 6 This is a schematic cross-sectional view showing one form of the semiconductor light emitting device according to the present embodiment.

[0034] Figure 7 (a) and (b) are diagrams showing a part of the manufacturing process of the side window cover involved in this embodiment. Figure 7 (a) is a schematic top view showing an unsintered multi-layer glass ceramic precursor, Figure 7 (b) is in Figure 7(a) is a schematic side view of a stack of unsintered multi-layer glass-ceramic precursors forming a side wall portion that faces a side wall portion that will become a window.

[0035] Figure 8 (a) to (c) are diagrams showing a part of the manufacturing process of the side window cover involved in this embodiment, Figure 8 (a) is sintering Figure 7 Schematic side view of the glass ceramic obtained by (b), Figure 8 (b) is in Figure 8 (a) is a schematic side view of a light-transmitting material provided on the obtained glass ceramic, Figure 8 (c) is a schematic top view showing the cutting lines when the multi-jointed side window covers are singulated. DETAILED DESCRIPTION

[0036] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with arbitrary modifications without departing from the gist of the present invention.

[0037] In the present specification, “to” indicating a numerical range means that the numerical values ​​described before and after the “to” are included as the lower limit and the upper limit.

[0038] The "average thermal expansion coefficient" or "thermal expansion coefficient" in this specification refers to a value measured as an average value of the ratio of elongation per 1°C when heating is performed in the range of 50 to 350°C.

[0039] <Side window cover>

[0040] The side window cover 10 according to the present embodiment is a member that covers a substrate on which a light-emitting element is provided and is sealed to the substrate.

[0041] The side window cover 10 has an upper wall portion 11, four side wall portions 12a, 12b, 12c, 12d, and a lower opening portion 3, and has a concave cross-section. Figure 1 and Figure 3 As shown, one side wall 12a of the four side walls is a window made of a light-transmitting material 1. The remaining three side walls 12b, 12c, 12d and the upper wall 11 of the four side walls are made of glass ceramics 2. In addition, Figure 1 is a schematic perspective view showing one form of the side window cover according to the present embodiment. Figure 3 This is its top view.

[0042] The four side walls are preferably perpendicular to the upper wall 11 , but strictly speaking, they do not need to be 90°, and may be considered perpendicular including manufacturing errors, etc. Specifically, the perpendicularity may be substantially perpendicular within a range of 90°±5°.

[0043] The light-transmitting material 1 and the glass ceramic 2 are directly bonded to each other.

[0044] Direct bonding refers to a state where the light-transmitting material 1 and the glass ceramic 2 are bonded without an adhesive layer of an organic material such as a resin layer. For example, heat welding, heat and pressure bonding, ultrasonic bonding, bonding using laser heating, optical contact, etc. are mentioned. Although bonding via bonding materials such as a metal intermediate layer and glass frit is also included in direct bonding, direct bonding without any bonding material is particularly preferred. In addition, Figure 2 yes Figure 1 A-A' line section view, but in Figure 2 , an example is shown in which the light-transmitting material 1 and the glass ceramic 2 are directly bonded together without using a bonding material such as a metal intermediate layer or glass glue.

[0045] By directly joining the light-transmitting material 1 and the glass ceramic 2, no organic material such as a resin layer is required, so the durability is excellent. In addition, it is also possible to suppress the generation of a small gap between the light-transmitting material 1 and the glass ceramic 2, and a high airtight seal can be achieved. Although a more detailed manufacturing method is described, by directly joining to make a multi-linked side window cover, then by cutting based on cutting, a plurality of side window covers can be obtained at one time. Therefore, the manufacturing process is simple and the productivity is also excellent.

[0046] The side window cover 10 of this embodiment forms the light extraction portion as a whole window by forming one side wall portion 12a of the four side walls as a window formed of the light-transmitting material 1. Therefore, compared with the method of Patent Document 1 in which the light extraction portion is small, high light extraction efficiency can be achieved.

[0047] In addition, the remaining three side wall portions 12b, 12c, and 12d of the above four side wall portions and the upper wall portion 11 are composed of glass ceramics 2. Glass ceramics have a higher Young's modulus than glass, and can suppress the deformation of the light-transmitting material 1, and the beam quality is stable. In addition, since the thickness of the side wall portion can be reduced, the volume of the lower opening portion 3 can be ensured, and the semiconductor light-emitting device can be miniaturized.

[0048] The light-transmitting material 1 constitutes the side wall portion 12a of the window of the side window cover 10, and allows light emitted from the light-emitting element to pass therethrough and be taken out to the outside. For example, it is preferable that the light-transmitting material 1 is transparent from the visible region to the near-infrared region.

[0049] Specifically, the light-transmitting material 1 is preferably glass, silicon or sapphire.

[0050] Silicon is preferred as the light-transmitting material 1 in terms of transmittance in the infrared region and heat resistance.

[0051] Sapphire is preferred as the light-transmitting material 1 in terms of mechanical strength and heat resistance.

[0052] Glass is preferred as the light-transmitting material 1 because it can be easily directly bonded to the glass ceramic 2 .

[0053] When glass is used as the light-transmitting material 1 , glass used as a window material of a conventional cavity can be used.

[0054] From the viewpoint of suppressing the increase of carbon residue during firing and hindering insulation, and from the viewpoint of heat resistance when sealed with the substrate of the light-emitting device, the glass transition temperature Tg of the glass is preferably 500°C or higher, more preferably 515°C or higher, and further preferably 520°C or higher, and the higher the better. In addition, the glass transition temperature Tg of the glass in this specification is the temperature at the first inflection point of the DTA chart obtained by differential thermal analysis (DTA).

[0055] From the viewpoint of preventing damage to the glass surface, the glass softening point Ts of the glass is preferably 700° C. or higher, more preferably 715° C. or higher, and further preferably 730° C. or higher, the higher the better. In addition, the glass softening point Ts of the glass in this specification is the temperature at the fourth inflection point of the DTA chart.

[0056] The average thermal expansion coefficient of glass is different from that of the glass ceramic 2, but is preferably 20×10 -7 ~99×10 -7 / °C. Here, from the viewpoint of the average thermal expansion coefficient of the substrate close to the mounted light emitting device, it is preferably 20×10 -7 / °C or more, more preferably 22×10 -7 / ℃ or more, and preferably 99×10 -7 / °C or less, more preferably 92×10 -7 / °C or less. In addition, the combination of the preferred upper and lower limit values ​​is arbitrary.

[0057] As glass satisfying the above characteristics, for example, soda-lime glass, borosilicate glass, aluminosilicate glass, etc. can be used. From the viewpoint of processability, borosilicate glass or aluminosilicate glass is preferred.

[0058] The light-transmitting material 1 may be subjected to appropriate surface treatment in order to efficiently extract light to the outside.

[0059] For example, it is preferable that an antireflection film is formed on at least one of the outer and inner surfaces of the light-transmitting material 1. Figure 4As shown, the antireflection film 5 is preferably formed on at least a portion of the inner side of the light-transmitting material 1, that is, on the surface on the side where the light-emitting element is provided, and is more preferably formed on at least a portion of the surfaces on both sides.

[0060] When the anti-reflection film 5 is formed on the inner side of the light-transmitting material 1, the anti-reflection film 5 is preferably formed on at least a portion of the region where the light-transmitting material 1 and the glass ceramic 2 are directly bonded. Figure 4 As shown, the antireflection film 5 is formed on the entire inner surface of the translucent material 1 . In this case, the antireflection film 5 is formed entirely in the region where the translucent material 1 and the glass ceramic 2 are directly bonded.

[0061] When the anti-reflection film 5 is formed on at least a portion of the region where the light-transmitting material 1 and the glass ceramic 2 are directly bonded, the direct bonding is preferably without any bonding material. In this case, the area of ​​the window that can be effectively utilized is maximized, and the loss of light emitted from the light-emitting element 22 is minimized.

[0062] The anti-reflection film 5 can use a conventionally known anti-reflection film that can at least reduce the reflectivity of light of the design wavelength. Among them, from the viewpoint of maintaining good anti-reflection performance even during the heat treatment when manufacturing the side window cover 10, a film composed of an inorganic material is preferred. Examples of the film composed of an inorganic material include a single-layer thin film, a laminated film such as SiO 2 And Ta 2 O 5 Such a dielectric multilayer film including two or more dielectric layers having different refractive indices, etc.

[0063] For the translucent material 1, other layers with certain functions can also be formed within the scope of not damaging the effect of the present invention. For example, a light diffusion layer, a conductive layer, etc. can be cited. From the viewpoint of airtight sealing, these other layers are preferably composed of inorganic materials. In addition, the light diffusion layer can also be directly formed by the surface processing of the translucent material 1.

[0064] The thickness of the light-transmitting material 1 is not particularly limited, and is preferably 200 μm to 1.5 mm, for example. Here, from the viewpoint of durability, the thickness is preferably 200 μm or more, more preferably 250 μm or more, and further preferably 300 μm or more. On the other hand, from the viewpoint of transmittance and miniaturization, the thickness of the light-transmitting material 1 is preferably 1.5 mm or less, more preferably 1.2 mm or less, and further preferably 1.1 mm or less. In addition, the combination of the preferred upper and lower limit values ​​is arbitrary.

[0065] Glass ceramics 2 are formed by dispersing filler components in a glass matrix.

[0066] From the perspective of verticality, it is preferred that the upper wall 11 and the three side walls 12b, 12c, and 12d formed by the glass ceramic 2 are integrated without a seam. This can be achieved by the manufacturing method described later, that is, a method of stacking a plurality of glass ceramic precursors and sintering them after opening the desired holes using a hole puncher, a method of forming the glass ceramic precursor using a mold and then sintering it. In this case, it is preferred that the upper wall 11 and the two side walls 12c and 12d are composed of the same glass ceramic, and it is more preferred that the upper wall 11 and the three side walls 12b, 12c, and 12d are composed of the same glass ceramic.

[0067] When the translucent material 1 is made of glass or sapphire and is bonded to the glass ceramic 2 without a metal intermediate layer, glass glue, etc., the glass softening point Ts of the glass matrix in the glass ceramic is preferably lower than the glass transition temperature Tg of the translucent material 1. Thus, the temperature during direct bonding can be lowered, and damage to the surface of the translucent material 1 can be suppressed.

[0068] The temperature difference between the glass transition temperature Tg of the light-transmitting material 1 and the glass softening point Ts of the glass matrix is, for example, 30 to 200° C. Here, from the above viewpoint, the temperature difference is preferably 30° C. or more, more preferably 35° C. or more, and further preferably 40° C. or more. The temperature difference is not particularly limited, but is, for example, 200° C. or less.

[0069] When the translucent material 1 is made of glass or sapphire and is bonded to the glass ceramic 2 via a glass glue, the glass softening point Ts of the glass glue is preferably lower than the glass transition temperature Tg of the translucent material 1. This can reduce the temperature during direct bonding and prevent damage to the surface of the translucent material 1.

[0070] Glass glue is a sealing glass made of low-melting-point glass, and any glass glue known in the past can be used. For example, low-melting-point glasses such as tin-phosphate glass, bismuth glass, vanadium glass, lead glass, zinc borate alkaline glass, and borosilicate glass can be preferably used. Among them, considering the reliability of adhesion, adhesion reliability, and airtight sealing, as well as the impact on the environment and human body, low-melting-point glasses made of tin-phosphate glass, bismuth glass, vanadium glass, and borosilicate glass are more preferred.

[0071] The specific glass softening point Ts of the glass matrix in the glass ceramic is preferably 450 to 1000°C. Here, the glass softening point Ts is preferably 1000°C or less, more preferably 950°C or less, and further preferably 900°C or less. In addition, from the viewpoint of suppressing the insulation impairment due to the increase of carbon residue during firing and the viewpoint of heat resistance during sealing with a substrate, the glass softening point Ts of the glass matrix is ​​preferably 450°C or more, more preferably 460°C or more, and further preferably 470°C or more. In addition, in this specification, the glass softening point Ts of the glass matrix is ​​the temperature at the fourth inflection point of the DTA chart of the glass monomer. In addition, the combination of the preferred upper and lower limit values ​​is arbitrary.

[0072] The glass matrix may be a conventionally known glass matrix, and preferably contains at least one of bismuth oxide and boron oxide, for example, preferably bismuth oxide-based glass or borosilicate-based glass.

[0073] As borosilicate glass, in addition to SiO 2 and B 2 O 3 In addition, CeO 2 ,RO,R' 2 O, R" 2 O 3 、R”'O 2 etc., preferably containing ZnO, K 2 O、Na 2 O.

[0074] In addition, in this specification, R refers to at least one selected from the group consisting of Zn, Ba, Sr, Mg, Ca, Fe, Mn, Cr, Sn, and Cu. R' refers to at least one selected from the group consisting of Li, Na, K, Cs, and Cu. R" refers to at least one selected from the group consisting of Al, Fe, and La. R'" refers to at least one selected from the group consisting of Zr, Ti, and Sn.

[0075] As bismuth oxide glass, in addition to Bi 2 O 3 In addition, it may also contain B 2 O 3 、CeO 2 、SiO 2 ,RO,R' 2 O, R" 2 O 3 、R”'O 2 wait.

[0076] However, any material may be used as long as it can be directly bonded to the light-transmitting material 1, and ceramics may be used instead of glass ceramics. Examples of ceramics include aluminum oxide and aluminum nitride.

[0077] The filler component can also use the existing known filler component, for example, preferably contains low thermal expansion filler, negative thermal expansion filler. By using low thermal expansion filler, negative thermal expansion filler, it is possible to maintain a good shape as the side window cover 10, and the close contact between the light-transmitting material 1 can also be improved. One filler can be used, or two or more fillers can be used.

[0078] Low thermal expansion fillers refer to fillers with a thermal expansion coefficient of 0 / ℃ or more and 40×10 -7 Fillers with a temperature of less than 1000 °C include, for example, zirconium oxide, silicon dioxide, and mixtures thereof. As a mixture, cordierite (2MgO·2Al 2 O 3 5SiO 2 )wait.

[0079] Negative thermal expansion fillers refer to fillers with a negative thermal expansion coefficient, that is, a filler with a thermal expansion coefficient less than 0 / °C, and examples thereof include zirconium phosphate, β-eucryptite (Li 2 O.Al 2 O 3 ·2SiO 2 ), zirconium tungstate (ZrW 2 O 8 )wait.

[0080] The total volume percentage of the filler components in the glass ceramic is preferably 25 to 65 volume %. Here, from the viewpoint of preventing cracks from occurring in the translucent material 1, the above-mentioned total volume percentage is, for example, preferably 25 volume % or more, more preferably 30 volume % or more, and further preferably 35 volume % or more. In addition, from the viewpoint of obtaining good adhesion with the translucent material 1, the total volume percentage of the filler components is preferably 65 volume % or less, more preferably 63 volume % or less, and further preferably 61 volume % or less. However, the above-mentioned content can be changed according to the specific gravity of the filler, etc. In addition, the combination of the preferred upper and lower limit values ​​is arbitrary.

[0081] The filler component is an inorganic powder, but the shape of the powder is not particularly limited, and examples thereof include spherical, flat, flaky, and fibrous shapes.

[0082] The size of the powder of the filler component is not particularly limited. For example, the 50% particle size (D 50 ) is preferably 0.5 to 10 μm. Here, the 50% particle size (D 50) is preferably 0.5 μm or more, more preferably 1 μm or more, and preferably 10 μm or less, more preferably 9 μm or less. In addition, the 50% particle size in this specification refers to the value measured by volume using a laser diffraction / scattering particle size distribution measuring device. In addition, the combination of the preferred upper and lower limits is arbitrary.

[0083] The average thermal expansion coefficient of the glass ceramic 2 is preferably 15×10 -7 ~75×10 -7 Here, from the viewpoint of the average thermal expansion coefficient of the substrate in the light emitting device to which the side window cover 10 is mounted, the average thermal expansion coefficient is preferably 15×10 -7 / °C or more, more preferably 16×10 -7 / ℃ or more, more preferably 17×10 -7 / °C or more. In addition, although it varies depending on the average thermal expansion coefficient of the light-transmitting material 1, the average thermal expansion coefficient is more preferably 75×10 -7 / °C or less, more preferably 70×10 -7 / °C or less, particularly preferably 65×10 -7 / °C or less. In addition, the combination of the preferred upper and lower limit values ​​is arbitrary.

[0084] From the viewpoint of preventing cracks and peeling of the translucent material 1 when the translucent material 1 and the glass ceramic 2 are directly bonded, the absolute value of the difference in average thermal expansion coefficient between the translucent material 1 and the glass ceramic 2 is preferably 24×10 -7 / °C or less, more preferably 22×10 -7 / ℃ or below, the smaller the better.

[0085] The upper surface composed of the upper wall portion 11 of the side window cover 10 and the upper end surface of the side wall portion 12a serving as the window is composed of glass ceramics 2 and a light-transmitting material 1. Similarly, the side surface composed of the two side wall portions 12c and 12d other than the side wall portion 12b located at a position opposite to the side wall portion 12a serving as the window and the left and right end surfaces of the side wall portion 12a serving as the window is also composed of glass ceramics 2 and a light-transmitting material 1.

[0086] However, the upper surface and the two side surfaces can form a smooth surface without generating a step difference between the end surface of the light-transmitting material 1 and the glass ceramic 2. This is because the side window cover 10 involved in this embodiment can obtain a plurality of side window covers 10 from a multi-joined side window cover by cutting after directly joining the light-transmitting material 1 and the glass ceramic 2.

[0087] Thus, the side window cover 10 is obtained by directly bonding the glass ceramic 2 and then cutting it instead of installing the light-transmitting material 1 later. This is useful not only from the perspective of productivity but also from the perspective of smoothness of the entire side window cover.

[0088] For the above reasons, the maximum height roughness Rz of the outer surface of the side window cover including the upper surface and the two side surfaces can be 50 μm or less. The maximum height roughness Rz can be 47 μm or less, or 45 μm or less.

[0089] When the side window cover is manufactured by laminating or inserting the light-transmitting material 1 to be a window into the singulated cavity from behind, the maximum height roughness Rz usually exceeds 150 μm.

[0090] In addition, the maximum height roughness Rz in this specification refers to an index of surface roughness, which is the sum of the height of the highest mountain and the depth of the deepest valley in the profile curve under the reference length, and is obtained in accordance with JIS B 0601: 2001. Specifically, the maximum height roughness Rz is a value obtained by measuring a measurement length of 3 mm with a cutoff wavelength of 0.8 mm using a surface roughness profile measuring machine SURFCOM.

[0091] like Figure 3 As shown, the lower opening 3 is a space surrounded by an upper wall 11 and four side walls 12a, 12b, 12c, and 12d, which is composed of a light-transmitting material 1 and glass ceramics 2. When the side window cover 10 involved in this embodiment is sealed to the substrate, it becomes a space (gap) for accommodating the light-emitting element.

[0092] The lower opening 3 is usually in the shape of a quadrangular prism, but can be set to any shape other than a quadrangular prism according to requirements, and can also be set to a shape different from the outer shape of the side window cover 10. For example, a semi-cylindrical shape and a polygonal prism shape can be cited. From the viewpoint of ease of processing, the shape of the lower opening 3 is preferably a quadrangular prism shape, that is, a hexahedral shape or a semi-cylindrical shape.

[0093] like Figure 5 As shown, the side window cover 10 preferably has a sealing material layer 4 on the lower end surfaces of the four side wall portions. The lower end surfaces of the four side wall portions refer to the end surfaces on the lower opening portion 3 side.

[0094] like Figure 6 As shown, the sealing material layer 4 is effective when the side window cover 10 is sealed to the substrate 21 provided with the light emitting element 22 so as to cover the light emitting element 22 to obtain the semiconductor light emitting device 20 .

[0095] exist Figure 5In the embodiment, the width of the sealing material layer 4 is narrower than the width of the lower end surfaces of the four side walls, but may be the same as the width of the lower end surfaces of the four side walls, and any width may be sufficient as long as sealing can be achieved.

[0096] The sealing material layer 4 is preferably a layer composed of a metal film or a layer composed of glass paste.

[0097] When the sealing material layer 4 is a layer composed of a metal film, the side window cover 10 and the substrate 21 can be hermetically sealed by sealing via a metal ring. Examples of the metal ring include a gold (Au)-tin (Sn) ring, a tin (Sn)-antimony (Sb) ring, a tin (Sn)-silver (Ag)-copper (Cu) ring, etc., but from the viewpoint of sealing performance, a gold tin ring is more preferred.

[0098] From the viewpoint of sealing performance when sealed via a metal ring, the layer composed of a metal film preferably has a layer containing one or more metal films selected from the group consisting of Au, Ag, Cu and Au-Sn alloy on its outermost surface, and more preferably has an Ag layer or an Au layer. The layer composed of a metal film may further have a film of Ni, Ti, Pd, Pt, Cu, etc. as a base of the layer of the metal film.

[0099] When the sealing material layer 4 is a layer made of glass paste, the side window cover 10 and the substrate 21 can be hermetically sealed by sealing by heating.

[0100] Glass glue is a sealing glass made of low-melting-point glass, and any known glass glue can be used. For example, low-melting-point glasses such as tin-phosphate glass, bismuth glass, vanadium glass, lead glass, and zinc borate alkali glass can be preferably used. Among them, considering the reliability of adhesion, adhesion reliability, and airtight sealing, as well as the impact on the environment and human body, low-melting-point glasses made of tin-phosphate glass, bismuth glass, and vanadium glass are more preferred.

[0101] The glass paste may further contain an inorganic filler such as an electromagnetic wave absorber or a low thermal expansion filler.

[0102] <Semiconductor light-emitting device>

[0103] The semiconductor light emitting device 20 involved in this embodiment includes a side window cover 10, a substrate 21, and a light emitting element 22 arranged on the substrate 21. The light emitting element 22 is hermetically sealed by integrating with the substrate 21 through the sealing material layer 4 at the lower end surface of the four side wall portions of the side window cover 10.

[0104] The side window cover 10 may be the side window cover described in the above-mentioned <Side window cover>, and the preferred aspects are also the same.

[0105] The sealing material layer 4 is preferably a layer composed of a metal film or a layer composed of glass glue, but is more preferably a layer composed of a metal film, and further preferably has an Ag layer or an Au layer on its outermost surface. The side window cover 10 and the substrate 21 are preferably integrated via the sealing material layer 4 as a layer composed of the above-mentioned metal film and the gold tin ring.

[0106] In the semiconductor light emitting device 20, the substrate 21 is not particularly limited as long as it has insulating properties, but is preferably a ceramic substrate from the viewpoint of heat dissipation. As the ceramic substrate, for example, an aluminum nitride (AlN) substrate, an aluminum oxide (AlO) substrate, or a ceramic substrate is preferred. 2 O 3 ) substrate, low temperature co-fired ceramics (LTCC: Low Temperature Co-fired Ceramics) substrate.

[0107] In the semiconductor light emitting device 20, the light emitting element 22 can use either the upper surface light emission or the end surface light emission. From the viewpoint of enjoying the effect of the present invention more, the end surface light emission is preferred. Figure 6 As shown, the light L emitted from the light emitting element 22 is in the horizontal direction, and an example thereof is a laser diode (LD). A window made of a light-transmitting material 1 is arranged on the side where the light is emitted from the light emitting element 22 .

[0108] Since the laser diode light has high straightness, there is a concern about light leakage from the side wall portion 12b that faces the side wall portion 12a that serves as a window. However, in the semiconductor light emitting device 20 according to the present embodiment, since the side wall portion 12b is made of glass ceramic, there is no concern about light leakage.

[0109] <Method for manufacturing side window cover>

[0110] The method for manufacturing the side window cover 10 according to the present embodiment is not particularly limited as long as the side window cover 10 having the features described in the above-mentioned <Side window cover> can be obtained.

[0111] An example of a method for manufacturing the side window cover 10 according to the present embodiment is shown below. In addition, the following manufacturing method is a method of obtaining a multi-jointed side window cover and cutting it by cutting to obtain individual side window covers. Although this method has excellent productivity, it does not exclude any method of manufacturing the side window covers one by one.

[0112] The manufacturing method of glass, silicon, sapphire, etc. used as the light-transmitting material 1 is not particularly limited, and any material may be manufactured or a commercially available material may be used. In addition, the light-transmitting material 1 may be provided with a layer having a function such as an antireflection film as required.

[0113] The manufacturing method of glass ceramics 2 is also not particularly limited, for example, can be obtained by forming and firing a precursor of glass ceramics, which is a mixture of glass powder and filler components that become a glass matrix. Specifically, the above-mentioned precursor can be formed into a sheet-like shape called a green sheet, and the method of firing can be enumerated.

[0114] When the glass ceramic 2 is produced using a glass ceramic precursor as a green sheet, a plurality of green sheets are stacked in a manner to achieve a desired height. Figure 7 As shown in (a), by using a hole puncher to open a plurality of holes 3' of a desired size and shape, a panel of an unsintered multi-layer glass ceramic precursor 2', which becomes an upper wall portion 11 and two opposing side walls 12c and 12d, can be obtained.

[0115] By stacking a plurality of green sheets to a desired height differently from the above, a panel of an unsintered glass ceramic precursor 2 ′ a that becomes the side wall portion 12 b facing the side wall portion 12 a that becomes the window can be obtained.

[0116] Through Figure 7 As shown in (b), the two panels obtained above are stacked and fired, and Figure 8 As shown in (a), a multi-jointed glass ceramic 2 having an upper wall portion 11 and three side walls 12b, 12c, and 12d without any joints can be obtained.

[0117] Next, by Figure 8 As shown in (b), the translucent material 1 is arranged relative to the obtained glass ceramic 2 so as to be in contact with the end faces of the glass ceramic that become the upper wall portion 11 and the two opposing side wall portions 12c and 12d, and directly joined, thereby obtaining a multi-jointed side window cover.

[0118] Examples of direct bonding include heat welding, heat and pressure bonding, ultrasonic bonding, bonding by laser heating, and optical contact.

[0119] Before directly joining the translucent material 1 to the glass ceramic 2, the end faces of the upper wall portion 11 and the two opposing side wall portions 12c, 12d of the glass ceramic 2 may be ground, etc., to reduce the surface roughness Ra. In addition, the surface of the translucent material 1 may also be ground to reduce the surface roughness Ra.

[0120] From the viewpoint of bonding after direct bonding, the surface roughness Ra of the end face and the surface of the light-transmitting material 1 is preferably 0.2 μm or less, and more preferably 0.1 μm or less. The surface roughness Ra of each end face and the light-transmitting material 1 need not be the same. In addition, the surface roughness Ra in this specification is a value measured in accordance with JIS B 0601:2001.

[0121] Afterwards, by Figure 8 The single dotted line shown in (c) is used as a cutting line to cut the plurality of side window covers 10 in a single piece. The cutting method is not particularly limited, but laser cutting using a laser, blade cutting using a dedicated blade, a method combining a plurality of cutting methods, etc. can be adopted. Among them, blade cutting is preferred from the viewpoint of cutting performance.

[0122] When the side window cover 10 is also provided with a sealing material layer 4, Figure 8 The single-dot dash line shown in (c) is used as a cutting line for cutting only in the direction of the center line including the lower opening 3. Then, after grinding the cut surface as required, a sealing material layer 4 is formed using a conventionally known sealing material by a conventionally known method.

[0123] The sealing material layer 4 may be formed by a printing method, a coating method using a dispenser, a dipping method, a laser metal deposition method, a method using a bonding wire, or the like.

[0124] Afterwards, by Figure 8 The other one of the one-dot chain lines shown in (c) is cut again as a cutting line, so that a plurality of side window covers 10 divided into pieces can be obtained.

[0125] In addition, in the above, the method of obtaining the side window cover by using the precursor of glass ceramic as a raw sheet is described, but it is also possible to obtain a multi-piece glass ceramic using a molding mold. In this case, as in the above, by directly joining the translucent material and then cutting it, a plurality of side window covers 10 implemented as a single piece can be obtained.

[0126] As mentioned above, the side window cover and the manufacturing method thereof according to the present embodiment have been described in detail. However, another aspect of the present embodiment is as follows.

[0127] [1] A side window cover, relative to a substrate on which a light-emitting element is provided, the side window cover covers the light-emitting element and is sealed to the substrate, wherein:

[0128] The side window cover has an upper wall portion, four side wall portions and a lower opening portion and has a concave cross-section.

[0129] One of the four side walls is a window made of a light-transmitting material.

[0130] Three of the four side walls and the upper wall are made of glass ceramics.

[0131] The light-transmitting material is directly bonded to the glass ceramic.

[0132] [2] In the side window cover described in [1] above,

[0133] The maximum height roughness Rz of the surface of the outer side of the side window cover is 50 μm or less.

[0134] [3] In the side window cover described in [1] or [2] above,

[0135] The light-transmitting material is glass, silicon or sapphire.

[0136] [4] In the side window cover described in any one of [1] to [3] above,

[0137] The absolute value of the difference between the average thermal expansion coefficient of the above-mentioned light-transmitting material and the above-mentioned glass ceramic at 50-350°C is 24×10 -7 / ℃ below.

[0138] [5] In the side window cover described in any one of [1] to [4] above,

[0139] An antireflection film is formed on at least one of the outer and inner surfaces of the light-transmitting material.

[0140] [6] In the side window cover described in any one of [1] to [5] above,

[0141] An antireflection film is formed on at least a portion of the inner surface of the light-transmitting material.

[0142] The antireflection film is also formed on at least a portion of the directly bonded region.

[0143] [7] In the side window cover described in any one of [1] to [6] above,

[0144] A sealing material layer is provided on the lower end surfaces of the four side wall portions.

[0145] [8] In the side window cover described in [7] above,

[0146] The sealing material layer is a layer composed of a metal film and has an Ag layer or an Au layer on its outermost surface.

[0147] [9] A semiconductor light emitting device, wherein:

[0148] A side window cover as described in [8], a substrate and a light emitting element arranged on the substrate,

[0149] The side window cover and the substrate are integrated via the sealing material layer and the gold-tin ring, and the light-emitting element is hermetically sealed.

[0150] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited thereto. Examples 1 to 3 are Examples, and Example 4 is a Comparative Example.

[0151] (Example 1)

[0152] As a light-transmitting material, a glass plate made of alkali-free borosilicate glass (EN-A1 manufactured by AGC Corporation) with a size of 50 mm × 50 mm × 0.7 mm was prepared. The glass transition temperature Tg of this glass is 710°C, and the thermal expansion coefficient at 50 to 350°C is 39 × 10 -7 / ℃.

[0153] As a precursor of glass ceramics, an inorganic powder is obtained by compounding and mixing a glass powder (ASF-1109 manufactured by AGC, glass softening point Ts = 537°C) as a glass matrix in a manner such that the volume % is 52%, and zirconium phosphate (ULTEA (registered trademark) WH2 manufactured by Toagosei Co., Ltd.) as a filler component is 48%. In the presence of an organic solvent, a plasticizer and a binder are mixed with the inorganic powder to prepare a slurry. The slurry is applied to a polyethylene terephthalate (PET) film using a doctor blade method and dried to produce a raw sheet. The thickness of each raw sheet is 200 μm.

[0154] 36 green sheets were stacked, and 8×8 square holes of 4.0 mm×4.0 mm were opened using a hole puncher, resulting in a multi-jointed panel consisting of 64 unsintered sheets. The panel was fired at 600°C to obtain a multi-jointed glass ceramic with 8×8 square holes of 3.4 mm×3.4 mm and a thickness of 6.3 mm. The thermal expansion coefficient of the obtained glass ceramic at 50-350°C was 36×10 -7 / ℃.

[0155] One surface of the glass ceramic having an opening formed by opening a quadrangular hole was polished to a surface roughness Ra of 0.1 μm or less.

[0156] Next, the multi-layered glass ceramics were arranged so that the surface having the opening of the glass ceramics was in contact with the glass plate composed of the above-mentioned alkali-free borosilicate glass as a light-transmitting material, and fired at 600°C for direct bonding to obtain a multi-layered side window cover.

[0157] For the multi-linked side window covers, use a blade to cut the 8-linked side window covers connected in 1×8 pieces from the glass plate side into 16 rows. Figure 8 As shown in (c), the cutting lines are a total of 17 center lines of the lower opening and center lines of the connecting parts between the openings and parallel thereto.

[0158] Since the cut surface based on the above cutting becomes the lower end surface of the four side walls of the cavity with the window frame, silver paste (manufactured by Daiken Chemical, US-202A) was screen-printed on the cut surface. For screen printing, a screen printing plate with a mesh size of 325 and an emulsion thickness of 10 μm was used. The pattern of the screen printing plate was a frame shape with a line width of 0.4 mm.

[0159] After screen printing, the film was dried at 70° C. for 30 minutes and then fired at 450° C. for 30 minutes, thereby forming a sealing material layer having a thickness of 7 μm and a line width of 0.4 mm on the lower end surfaces of the four side walls.

[0160] Next, the sheet was cut again using a total of nine center lines of the connection portions between the openings that were orthogonal to the cutting lines in the first cutting as cutting lines, and was singulated to obtain 128 side window covers having a sealing material layer formed thereon.

[0161] The size of each side window cover is that the upper surface is 4.8mm×6.9mm, 0.7mm of the 6.9mm is the upper end surface of the glass forming the side wall portion 12a of the window, and 6.2mm is the upper wall portion 11 composed of glass ceramics. The side surface that becomes the window and the side surface opposite to it are both 2.2mm in height and 4.8mm in width. The remaining two side surfaces are both 2.2mm in height and 6.9mm in width, 0.7mm of the 6.9mm is the left and right end surfaces of the glass forming the side wall portion 12a of the window, and 6.2mm is the side wall portions 12c and 12d composed of glass ceramics. The glass ceramics and glass are both 0.7mm thick, and the size of the lower opening 3 is 3.4mm×5.5mm, and the height is 1.5mm.

[0162] On the other hand, an aluminum nitride (AlN) substrate (manufactured by MARUWA Co., Ltd., AN-170, 7.5 mm×7.5 mm×0.635 mm) with an Au / Pt / Ti film formed on the surface was prepared. The side window cover with the sealing material layer obtained above was sealed via a gold tin ring on the side of the substrate with the Au / Pt / Ti film formed on it. The sealing conditions were 280°C for 60 seconds in a nitrogen environment.

[0163] When the sealed side window cover with substrate was subjected to a He bombardment leakage test, the leakage was 3.0×10 -10 Pa·m 3 / s, no leakage was confirmed and the airtight sealing was good.

[0164] (Example 2)

[0165] As a light-transmitting material, a 50 mm × 50 mm × 0.7 mm glass plate made of borosilicate glass (manufactured by SCHOTT, D263 (registered trademark) T eco) was prepared. The glass transition temperature Tg of this glass is 566°C, and the thermal expansion coefficient at 50 to 350°C is 72×10 -7 / °C. In addition, an antireflection film is formed on the entire surface of both surfaces of the glass by a vapor deposition method.

[0166] As a precursor of glass ceramics, an inorganic powder is obtained by mixing and blending a glass powder (AGC, KF9173, glass softening point Ts = 480°C) as a glass matrix in a manner of 75% by volume and cordierite (Marusu Glaze) as a filler component in a manner of 25% by volume. In the presence of an organic solvent, a plasticizer and a binder are mixed with the inorganic powder to prepare a slurry. The slurry is applied to a polyethylene terephthalate (PET) film by a doctor blade method and dried to produce a green sheet. The thickness of each green sheet is 200 μm.

[0167] 36 green sheets were stacked, and 8×8 square holes of 4.0 mm×4.0 mm were opened using a hole puncher to obtain a multi-jointed panel consisting of 64 unsintered sheets. The panel was fired at 600°C to obtain a multi-jointed glass ceramic with 8×8 square holes of 3.4 mm×3.4 mm and a thickness of 6.3 mm. The thermal expansion coefficient of the obtained glass ceramic at 50-350°C was 68×10 -7 / ℃.

[0168] One surface of the glass ceramic having an opening formed by opening a quadrangular hole was polished to a surface roughness Ra of 0.1 μm or less.

[0169] Next, the multi-layered glass ceramics are arranged so that the surface of the glass ceramic having the opening is in contact with the glass plate composed of the above-mentioned borosilicate glass as a light-transmitting material, and are fired at 550°C to directly bond them to obtain a multi-layered side window cover.

[0170] For the multi-linked side window covers, use a blade to cut the 8-linked side window covers connected in 1×8 pieces into 16 rows from the glass plate side. Figure 8As shown in (c), the cutting lines are the center line of the lower opening and the center lines of the connecting parts between the openings and the openings parallel thereto, a total of 17.

[0171] Since the cut surface based on the above cutting becomes the lower end surface of the four side walls of the cavity with the window frame, silver paste (manufactured by Daiken Chemical, US-202A) was screen-printed on the cut surface. For screen printing, a screen printing plate with a mesh size of 325 and an emulsion thickness of 10 μm was used. The pattern of the screen printing plate was a frame shape with a line width of 0.4 mm.

[0172] After screen printing, the film was dried at 70° C. for 30 minutes and then fired at 450° C. for 30 minutes, thereby forming a sealing material layer having a thickness of 7 μm and a line width of 0.4 mm on the lower end surfaces of the four side walls.

[0173] Next, the sheet was cut again using a total of nine center lines of the connection portions between the openings that were orthogonal to the cutting lines in the first cutting as cutting lines, and was separated into pieces to obtain 128 side window covers having a sealing material layer formed thereon.

[0174] The size of each side window cover is 4.8mm×6.9mm on the top surface, 0.7mm of which is the upper end surface of the glass forming the side wall 12a of the window, and 6.2mm is the upper wall 11 made of glass ceramics. The side surface that becomes the window and the side surface opposite to it are both 2.2mm in height and 4.8mm in width. The remaining two side surfaces are both 2.2mm in height and 6.9mm in width, 0.7mm of which is the left and right end surfaces of the glass forming the side wall 12a of the window, and 6.2mm is the side wall 12c, 12d made of glass ceramics. The glass ceramics and glass are both 0.7mm thick, and the size of the lower opening 3 is 3.4mm×5.5mm, with a height of 1.5mm.

[0175] (Example 3)

[0176] As a light-transmitting material, a 50 mm × 50 mm × 0.7 mm plate made of sapphire (both sides mirror-polished) was prepared. The thermal expansion coefficient of sapphire at 50 to 350°C is 76 × 10 -7 / ℃.

[0177] As a precursor of glass ceramics, inorganic powder is obtained by mixing and blending glass powder (AGC, ASF-1860, glass softening point Ts = 830°C) as a glass matrix to 42% by volume and alumina as a filler component to 58% by volume. By adding an appropriate amount of paraffin wax to the inorganic powder, heating and pressurizing in a mold, a multi-linked pressed powder glass ceramic with a 3.2 mm × 3.2 mm square hole and 8 × 8 holes and a thickness of 6.3 mm is obtained.

[0178] One surface of the glass ceramic having an opening formed by opening a quadrangular hole was polished to a surface roughness Ra of 0.1 μm or less.

[0179] The glass ceramic after grinding was printed with glass glue and fired at 580° C. The same glass glue was printed and fired for the sapphire plate.

[0180] Next, the multi-layered glass ceramics were arranged so that the surface having the opening of the glass ceramics was in contact with the plate made of the sapphire as the light-transmitting material, and fired at 680° C. to directly bond them, thereby obtaining a multi-layered side window cover.

[0181] For the multi-linked side window covers, use a blade to cut the 8-linked side window covers connected in 1×8 quantities from the sapphire plate side into 16 rows. Figure 8 As shown in (c), the cutting lines are the center line of the lower opening and the center lines of the connecting parts between the openings and the openings parallel thereto, a total of 17.

[0182] Since the cut surface based on the above cutting becomes the lower end surface of the four side walls of the cavity with the window frame, silver paste (manufactured by Daiken Chemical, US-202A) was screen-printed on the cut surface. For screen printing, a screen printing plate with a mesh size of 325 and an emulsion thickness of 10 μm was used. The pattern of the screen printing plate was a frame shape with a line width of 0.4 mm.

[0183] After screen printing, the film was dried at 70° C. for 30 minutes and then fired at 450° C. for 30 minutes, thereby forming a sealing material layer having a thickness of 7 μm and a line width of 0.4 mm on the lower end surfaces of the four side walls.

[0184] Next, the sheet was cut again using a total of nine center lines of the connection portions between the openings that were orthogonal to the cutting lines in the first cutting as cutting lines to separate the sheets, thereby obtaining 128 side window covers having a sealing material layer formed thereon.

[0185] The size of each side window cover is 4.8mm×6.9mm on the top surface, 0.7mm of which is the upper end surface of the sapphire forming the side wall 12a of the window, and 6.2mm is the upper wall 11 made of glass ceramic. The side surface that becomes the window and the side surface opposite to it are both 2.2mm in height and 4.8mm in width. The remaining two side surfaces are both 2.2mm in height and 6.9mm in width, 0.7mm of which is the left and right end surfaces of the sapphire forming the side wall 12a of the window, and 6.2mm is the side wall 12c and 12d made of glass ceramic. The glass ceramic and sapphire are both 0.7mm thick, and the size of the lower opening 3 is 3.4mm×5.5mm, with a height of 1.5mm.

[0186] (Example 4)

[0187] As a light-transmitting material, a 50 mm × 50 mm × 0.7 mm plate made of sapphire (both sides mirror-polished) was prepared. The thermal expansion coefficient of sapphire at 50 to 350°C is 76 × 10 -7 / ℃.

[0188] As a precursor of glass ceramics, an inorganic powder is obtained by compounding and mixing a glass powder (ASF-1109 manufactured by AGC, glass softening point Ts = 537°C) as a glass matrix in a manner of 52% by volume and a zirconium phosphate (ULTEA (registered trademark) WH2 manufactured by Toagosei Co., Ltd.) as a filler component in a manner of 48% by volume. In the presence of an organic solvent, a plasticizer and a binder are mixed with the inorganic powder to prepare a slurry. The slurry is applied to a polyethylene terephthalate (PET) film using a doctor blade method and dried to produce a raw sheet. The thickness of each raw sheet is 200 μm.

[0189] 36 green sheets were stacked, and 8×8 square holes of 4.0 mm×4.0 mm were opened using a hole puncher to obtain a multi-jointed panel consisting of 64 unsintered sheets. The panel was fired at 600°C to obtain a multi-jointed glass ceramic with 8×8 square holes of 3.4 mm×3.4 mm and a thickness of 6.3 mm. The thermal expansion coefficient of the obtained glass ceramic at 50-350°C was 36×10 -7 / ℃.

[0190] One surface of the glass ceramic having an opening formed by opening a quadrangular hole was polished to a surface roughness Ra of 0.1 μm or less.

[0191] Next, a direct bonding attempt was made by configuring a multi-layer glass ceramic so that the surface with the opening of the glass ceramic was in contact with the sapphire plate as the light-transmitting material and firing the glass ceramic at 600°C. However, bonding was not possible due to the difference in thermal expansion coefficients between sapphire and glass ceramic.

[0192] Although the present invention has been described in detail with reference to specific embodiments, it is obvious to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on the invention of Japanese patent application (Japanese Patent Application No. 2022-102030) filed on June 24, 2022, and its contents are incorporated herein by reference.

[0193] Description of reference numerals:

[0194] 1…light-transmitting material; 2…glass ceramics; 2', 2'a…precursor of glass ceramics; 3…lower opening; 3'…hole; 4…sealing material layer; 5…anti-reflection film; 10…side window cover; 11…upper wall; 12, 12a, 12b, 12c…side wall; 20…semiconductor light-emitting device; 21…substrate; 22…light-emitting element; L…outgoing light.

Claims

1. A side window cover, relative to a substrate provided with a light-emitting element, the side window cover covers the light-emitting element and is sealed to the substrate, in, The side window cover has an upper wall portion, four side wall portions and a lower opening portion, and has a concave cross-section. One of the four side walls is a window made of a light-transmitting material. Three of the four side walls and the upper wall are made of glass ceramics. The light-transmitting material is directly bonded to the glass ceramic.

2. The side window cover according to claim 1, wherein: The maximum height roughness Rz of the surface of the outer side of the side window cover is 50 μm or less.

3. The side window cover according to claim 1 or 2, wherein: The light-transmitting material is glass, silicon or sapphire.

4. The side window cover according to claim 1 or 2, wherein: The absolute value of the difference between the average thermal expansion coefficient of the light-transmitting material and the glass ceramic at 50 to 350° C. is 24×10 -7 / ℃ below.

5. The side window cover according to claim 1 or 2, wherein: An antireflection film is formed on at least one of the outer and inner surfaces of the light-transmitting material.

6. The side window cover according to claim 1 or 2, wherein: An antireflection film is formed on at least a portion of the inner surface of the light-transmitting material. The antireflection film is also formed on at least a portion of the directly bonded region.

7. The side window cover according to claim 1 or 2, wherein: A sealing material layer is provided on the lower end surfaces of the four side walls.

8. The side window cover according to claim 7, wherein: The sealing material layer is a layer composed of a metal film and has an Ag layer or an Au layer on its outermost surface.

9. A semiconductor light emitting device, wherein: A side window cover according to claim 8, a substrate and a light emitting element arranged on the substrate, The side window cover and the substrate are integrated via the sealing material layer and the gold-tin ring, and the light-emitting element is hermetically sealed.

Citation Information

Patent Citations

  • Light emitting device and method of manufacturing light emitting device

    JP2009289775A

  • Light source device

    JP2021057459A

  • Rubber composition for golf ball core, and golf ball

    JP2022102030A

  • Package for mounting electrical element, array package and electrical device

    WO2018030486A1